HCV Replicon Systems: Workhorses of Drug Discovery and Resistance - Shaheen Khan; Shalini Soni; Naga Suresh Veerapu (Frontiers in Cellular and Infection Microbiology, 2020)
The development of direct-acting antivirals (DAAs) has revolutionized the state-of-the art treatment of HCV infections, with sustained virologic response rates above 90%. However, viral variants harboring substitutions referred to as resistance-associated substitutions (RASs) may be present in baseline levels and confer resistance to DAAs, thereby posing a major challenge for HCV treatment. HCV replicons have been the primary tools for discovering and evaluating the inhibitory activity of DAAs against viral replication. Interest in replicon systems has further grown as they have become indispensable for discovering genotype-specific and cross-genotype RASs. Here, we review functional replicon systems for HCV, how these replicon systems have contributed to the development of DAAs, and the characteristics and distribution of RASs for DAAs.